Evaluation of The Drinking Water Management Program Using Seawater Reverse Osmosis Technology on Penyengat Island, 2022–2025 - Megawati Romaulina Napitupulu; Eki Darmawan; Khairi Rahmi (Anthroposia: Journal of Social and Human Development, 2026)
The people of Penyengat Island face a shortage of clean water, which the government addresses through a clean water management program using Sea Water Reverse Osmosis technology to meet the island's clean water needs. The Technical Implementation Unit of the Public Works and Public Housing Office is responsible for the operation, maintenance, and rehabilitation of infrastructure related to SWRO management. This study aims to evaluate the implementation of the clean water management program using Sea Water Reverse Osmosis (SWRO) technology, as well as the challenges faced in providing clean water on Penyengat Island. The research method used is descriptive qualitative, which serves to describe the reality of events occurring in the field for this study using primary and secondary data. Primary data is collected through observation and interviews. This research was carried out through direct observation at the Sea Water Reverse Osmosis (SWRO) system operation site on Penyengat Island and interviews with informants from the Ministry of Public Works and Housing (PUPR) of Tanjungpinang City, the PUPR Office of Tanjungpinang City, BLUD UPTD SPAM, and the local community. Secondary data were obtained from the Mayor's regulations, legislation, scientific papers, program implementation reports, and the official website of Tanjungpinang City Government. Data collection was done through observation, interviews, and documentation, while analysis was conducted through data reduction, data presentation, and drawing conclusions. Based on Pietrzak's Program Evaluation theory, the results show that the program is not yet optimal due to limitations in storage tanks, damaged distribution pipes, insufficient human resources, and limited operational budgets. These conditions have caused water distribution to not be able to occur 24 hours a day and it is still carried out on a rotation basis. Even so, the presence of SWRO services has improved people's access to clean water, so daily needs can be met better.